Composites of yeast glucan particles and curcumin lead to improvement of dextran sulfate sodium-induced acute bowel inflammation in rats - Rotrekl, Dominik; Šalamúnová, Petra; Paráková, Lenka; Baďo, Ondrej; Saloň, Ivan; Štěpánek, František; Hanuš, Jaroslav; Hošek, Jan (Carbohydrate polymers, 2021)
[Display omitted] •Glucan particles with loaded curcumin were used to treat bowel inflammation in vivo.•Prepared composites were analysed by microscopy techniques and by XRD analysis.•Glucan particles with incorporated curcumin were able to relieve symptoms of colitis.•Prepared composites decrease the level of pro-inflammatory cytokines and enzymes. The goal of this work was to assess the usability of yeast glucan particles (GPs) as carriers for curcumin and determine the beneficial effect of a pharmacological composite of curcumin in GPs on dextran sulfate sodium induced colitis in rats. The assessment of the anti-inflammatory effect of particular substances was evaluated on the basis of the calculated disease activity index and by assessment of cytokines and enzymes from the gut tissue – tumor necrosis factor α (TNF-α), transforming growth factor β1, interleukin (IL)-1β, IL-6, IL-10, IL-17, catalase, superoxide dismutase 2, myeloperoxidase (MPO), and matrix metalloproteinase 9. Composites of GPs with incorporated curcumin showed promising results with the capability to lower symptoms of colitis and significantly decrease the production of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and the activity of MPO, as well. The anti-inflammatory effect of the composites was greater than those of pure GPs or curcumin.